2000
DOI: 10.1002/etc.5620190434
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the probability of detecting organochlorine pesticides and polychlorinated biphenyls in stream systems on the basis of land use in the Pacific Northwest, USA

Abstract: Abstract-We analyzed streambed sediment and fish tissue (Cottus sp.) at 30 sites in the Puget Sound and Willamette basins in Washington and Oregon, USA, respectively, for organochlorine pesticides and polychlorinated biphenyls (PCBs). The study was designed to determine the concentrations of organochlorine pesticides and PCBs in fish tissue and sediment by land use within these basins and to develop an empirical relation between land use and the probability of detecting these compounds in fish tissue or sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…At the national scale, impacts transmitted through habitat and water quality were essentially of equal magnitude. This is consistent with results of many earlier studies that have shown that land use is correlated with changes in both stream channel characteristics (Richards et al 1996, Wang et al 1997, Fitzpatrick et al 2001, Stewart et al 2001, Goldstein et al 2007) and water quality (Hunsaker and Levine 1995, Johnson et al1997, Black et al 2000. And further, that both basin-and local reach-scale processes were implicated in the causal structure that generated both habitat and water quality impacts , Lammert and Allan 1999, Zorn et al 2002, Black et al 2004, Hutchens et al 2009, Baker and Wiley 2009).…”
Section: National Modelsupporting
confidence: 90%
“…At the national scale, impacts transmitted through habitat and water quality were essentially of equal magnitude. This is consistent with results of many earlier studies that have shown that land use is correlated with changes in both stream channel characteristics (Richards et al 1996, Wang et al 1997, Fitzpatrick et al 2001, Stewart et al 2001, Goldstein et al 2007) and water quality (Hunsaker and Levine 1995, Johnson et al1997, Black et al 2000. And further, that both basin-and local reach-scale processes were implicated in the causal structure that generated both habitat and water quality impacts , Lammert and Allan 1999, Zorn et al 2002, Black et al 2004, Hutchens et al 2009, Baker and Wiley 2009).…”
Section: National Modelsupporting
confidence: 90%
“…Conversely, TIs for vertebrates and macroinvertebrates improved as forested land use increased or agricultural use decreased, but not in a statistically significant manner (p B 0.10). Despite this lack of significance, these results are consistent with reports by others (Black et al 2000) identifying that specific land uses are sources of relatively more (urban, agricultural) or fewer (forested) chemical stressors. They further suggest that chemical-management practices on agricultural and urban lands must be robust and that large forested areas with undisturbed soil organic matter are needed to function as chemical sinks limiting the migration of chemicals (particularly those being atmospherically deposited) to adjacent waters.…”
Section: Land Use Versus Acute Tissupporting
confidence: 91%
“…Land use (urban, agricultural, forested) has been shown to be a major determinant of the type and quantity of chemical stressors entering and potentially affecting aquatic systems (Anderson et al 1996a, b;Waite et al 2008;Black et al 2000). Oregon land zoning data and land ownership layers were combined with 2007 USGS satellite imagery using a geographic information system to create a land use layer for the basin.…”
Section: Biological Condition Sites and Datamentioning
confidence: 99%
“…Black et al [38] identified a significant relation between organochlorine pesticides in fish tissue and percentage urban and agricultural land use. However, they did not find a similar significant relation with land use and streambed sediment pesticide concentrations.…”
Section: Discussionmentioning
confidence: 99%